2015
DOI: 10.1016/j.sleep.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associations of respiratory-related leg movements: the MrOS sleep study

Abstract: Objectives Obstructive respiratory events often terminate with an associated respiratory-related leg movement (RRLM). Such leg movements are not scored as periodic leg movements (PLMS), though the criteria for distinguishing RRLM from PLMS differ between American Academy of Sleep Medicine (AASM) and World Association of Sleep Medicine (WASM)/ International Restless Legs Syndrome Study Group (IRLSSG) scoring manuals. Such LMs may have clinical significance in patients with obstructive sleep apnea (OSA). We exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The absence of snoring, however, makes apnea unlikely; only 6% of apnea patients do not snore [ 29 ]. Insomnia and restless legs syndrome are each clinically significant in 5–10% of adults in general population, and an average incidence of 23% of respiratory-related leg movements has been documented in a sleep apnea cohort [ 33 35 ]. According to this study, insomnia and restless legs are more frequent in OI population than among unaffected peers.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of snoring, however, makes apnea unlikely; only 6% of apnea patients do not snore [ 29 ]. Insomnia and restless legs syndrome are each clinically significant in 5–10% of adults in general population, and an average incidence of 23% of respiratory-related leg movements has been documented in a sleep apnea cohort [ 33 35 ]. According to this study, insomnia and restless legs are more frequent in OI population than among unaffected peers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in patients with RLS, it has been shown that only the periodic LMs respond to dopaminergic treatment and that non-periodic LMs with IMIs <5 s are unaffected [44]. On the other hand, LMs associated with respiratory events may be associated with clinical variables independent of PLMS, such as number of apnea episodes, presence of chronic obstructive pulmonary disease, hypertension and ethnic factors [45]. Thus, the investigation of nocturnal non-periodic leg movement activity deserves further attention.…”
Section: Identifying Quantifying and Scoring Plms And Their Associatmentioning
confidence: 99%
“…That glucose is again released into the blood circulation and taken up by muscles, where it is converted to pyruvate 12 . OSA is known to be associated with increased night-time muscle activity, due to either respiratory-related leg movements secondary to obstructive respiratory events 13 or bathroom visits because of nocturia 3 . Although significantly higher in patients with OSA than in control individuals in our study, the night-time levels of Ala in OSA patients remained nearly stable and not deviating from the evening levels ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%